2021
DOI: 10.31234/osf.io/a9unf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Environments, Psychosocial Health, and Health Behaviors in a Crisis – A Scoping Review of the Literature in the COVID-19 Context

Abstract: The COVID-19 outbreak has led to major restrictions globally, affecting people’s psychosocial health and their health behaviors. Thus, the purpose of this scoping review was to summarize the available research regarding the nature-health-association in the COVID-19 context. Keywords related to natural environments and COVID-19 were combined to conduct a systematic online search in six major databases. Eligibility criteria were a) published since 2020 with data collected in the COVID-19 context b) peer-reviewed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
(105 reference statements)
0
4
0
1
Order By: Relevance
“…Our analyses and evaluation complement existing systematic (Labib et al, 2022) and scoping reviews (Heckert & Bristowe, 2021;Nigg et al, 2021) conducted throughout the pandemic on the effects of nature and green spaces on mental health. These effects also reinforce pre-COVID-19 research that observed similar health outcomes in more general contexts (Lackey et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our analyses and evaluation complement existing systematic (Labib et al, 2022) and scoping reviews (Heckert & Bristowe, 2021;Nigg et al, 2021) conducted throughout the pandemic on the effects of nature and green spaces on mental health. These effects also reinforce pre-COVID-19 research that observed similar health outcomes in more general contexts (Lackey et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Although several previous reviews have examined the evidence regarding associations between nature exposure and mental health during the COVID-19 pandemic (Labib et al, 2022;Nigg et al, 2021), this is the first study to conduct a robust review of these relationships that accounts for the risk of bias and the quality of evidence presented. Fifty-nine articles published over nearly two-and-half years of High the pandemic were evaluated, assessing 12 unique mental health outcomes accounting for up to four different dimensions of nature exposure: nature availability, access to nature, contact with nature, and nature at home.…”
Section: Discussionmentioning
confidence: 99%
“…The answer could be important because it will influence the pattern of our urban design in the near future. Large flexible spaces can be seen as a valuable resource as they have so many uses, like an evacuation site during an earthquake or other kinds of catastrophe [5]. In Vancouver, New York, and London, large green spaces and convention centers have been transformed into emergency field hospitals.…”
Section: Results and Analysismentioning
confidence: 99%
“…In other words, since public parks do not have monetary value and take up large swaths of land, there is little incentive for self-interested private developers to provide them within a free market without government intervention. So the size of the green space mainly depends on the policies of local governments and residents' demands [5].…”
Section: Size and Distance Of The Proximity Of Green Spacementioning
confidence: 99%
“…Diante disso, as áreas verdes urbanas tornaram-se muito importantes para a boa disposição mental e física das populações urbanas durante a pandemia. No entanto, os decretos que determinaram o isolamento social influenciaram o comportamento humano em relação às áreas verdes (NIGG;PETERSEN;MACINTYRE, 2021). Dependendo das medidas de contenção em vigor, algumas pessoas frequentaram menos as áreas verdes e outras mais (DERKS;GIESSEN;WINKEL, 2020;UGOLINI et al, 2020;VENTER et al, 2020).…”
Section: Introductionunclassified